Facile synthesis of perovskite ZIF67 derivative using ammonia fluoride and comparison with post-treated ZIF67 derivatives on energy storage ability. (1st September 2021) - Lee, Pin-Yan; Lin, Lu-Yin; Hsu, I-Jui; Chan, Chong-You; Lee, Jyh-Fu; Sheu, Hwo-Shuenn
Highlights: Novel ZIF67-derived perovskite fluorides were synthesized using ammonium fluoride. Perovskite fluoride shows particle-aggregated particle with less grain boundaries. Highest CF of 490.4 F/g is got for a ZIF67-derived perovskite fluoride electrode. The untreated ZIF67 electrode only shows CF value of 3.5 F/g at 20 mV/s. Replace 2-methylimidazole with F − in ZIF67 can improve electrical conductivity. Abstract: Oxidation, carbonization, sulfurization and selenization are commonly used to enhance electrical conductivity and electroactivity of metal–organic frameworks. However, extra costs on time and money are required for post treatments. In this work, ammonium fluoride (NH4 F) is incorporated in precursor solution for synthesizing perovskite ZIF67 derivatives as electroactive material. Novel particle-aggregated particle is obtained with largely reduced sizes and less grain boundaries. A highest specific capacitance (CF ) of 490.4 F/g is attained at 20 mV/s for the optimized ZIF67 derivative electrode prepared using NH4 F and Co:Ni ratio of 2:1 (CoNi21-NH4 F), while the untreated, oxidized, carbonized, sulfurized and selenized bimetallic ZIF67 electrodes synthesized without NH4 F only show the smaller CF values of 3.5, 363.9, 28.7, 85.9 and 103.2 F/g at 20 mV/s, respectively. Replacing 2-methylimidazole with F − in ZIF67 can improve electrical conductivity due to smaller size and higher electronegativity of F − than 2-methylimidazole. Largely enhanced CF value for CoNi21-NH4 F electrode strongly indicates success of improving energy storage via simply adding NH4 F in precursor solution without post treatments. Maximum energy density of 22.7 Wh/kg at power density of 0.6 W/kg, CF retention of 94% and Coulombic efficiency of 99% in 10.000 cycles charge/discharged process are obtained for supercapacitor with CoNi21-NH4 F electrodes. Graphical abstract: Image, graphical abstract